ANALISIS LAYANAN FISIOTERAPI DALAM UPAYA PELAYANAN KESEHATAN DI PUSKESMAS WILAYAH DKI JAKARTA: Analisis Layanan Fisioterapi di Puskesmas Wilayah DKI Jakarta - Vetty Yulianty Permanasari; Putri Karina Syafitri (Jurnal Ilmiah Fisioterapi, 2020)
The increase in NCD’s such as hypertension, stroke, diabetes mellitus, joint disease, lack of physical activity, injury, and disability in line with the increasing need for physiotherapy services in health facilities including in Community Health Centers. The role of physiotherapist in the Community Health Centers according to Permenkes No. 65 of 2015 is to carry out activities in the form of promotive and preventive without prejudice to curative and rehabilitative. The purpose of this study is to analyze physiotherapy services at the Community Health Centers using a system approach seen through 5 levels prevention measures namely are health promotion, specific protection, early diagnosis and prompt treatment, disability limitation and rehabilitation efforts at 6 Puskesmas in DKI Jakarta. This study uses qualitative research methods through a phenomenological approach. The results of this study obtained a depth-overview of the efforts of health services at the Physiotherapy Services, namely the provision of medical services is preferred over promotive and preventive efforts. Physiotherapy services at the Puskesmas have been regulated in the Decree of the Puskesmas Head by referring to Permenkes No. 75 of 2014. Public health activities in collaboration with the Physiotherapy Services at the Puskesmas are only carried out by 3 Puskesmas and some of them only conduct individual services. This study recommends that adding 1 physiotherapist HR to be able help physiotherapy services outside the building and physiotherapy organizations can create specialized public health training to support physiotherapy competencies. Keywords: Community Health Centers, Physiotherapy services, Five levels prevention